2020
DOI: 10.1093/ndt/gfaa142.p1030
|View full text |Cite
|
Sign up to set email alerts
|

P1030endothelial Dysfunction and Cardiac Valve Calcification in Patients With Diabetic Kidney Disease Undergoing Chronic Hemodialysis

Abstract: Background and Aims The character of endothelial dysfunction (ED), especially of nitric oxide (NO) system, in patients with diabetic kidney disease (DKD) undergoing chronic hemodialysis (HD) was not asserted enough. In this condition not clearly established the relationship of structural and functional activity of endothelium with the presence and severity of cardiac valve calcification (CVC) as independent predictor of cardiovascular morbidity and mortality. The purpose of the current study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…29,30 Tang et al, 31 reported increased cardiac valvular calcification assessed by echocardiography and valvular regurgitation in T2D patients with DKD compared to another diabetic group without DKD. Litovkina et al, 32 also reported increased incidence of cardiac valvular calcification assessed by echocardiography mainly MAC and AVC in DKD patients on chronic hemodialysis.…”
Section: Cardiac Valvular Calcification In Relation To Inactive Mgp L...mentioning
confidence: 95%
“…29,30 Tang et al, 31 reported increased cardiac valvular calcification assessed by echocardiography and valvular regurgitation in T2D patients with DKD compared to another diabetic group without DKD. Litovkina et al, 32 also reported increased incidence of cardiac valvular calcification assessed by echocardiography mainly MAC and AVC in DKD patients on chronic hemodialysis.…”
Section: Cardiac Valvular Calcification In Relation To Inactive Mgp L...mentioning
confidence: 95%